Bioinformatics-based study reveals that AP2M1 is regulated by the circRNA-miRNA-mRNA interaction network and affects Alzheimer’s disease - Zhang, Qi; Chen, Bishuang; Yang, Ping; Wu, Jipan; Pang, Xinping; Pang, Chaoyang (Frontiers in Genetics, 2022)
Alzheimer's disease (AD) is a chronic neurological illness that worsens with time. Extracellular senile plaques created by -amyloid protein deposition, neurofibrillary tangles formed by tau protein hyperphosphorylation, and neuronal loss with glial cell hyperplasia are the hallmark diseases. Accumulating evidence indicates that noncoding RNAs are strongly implicated in associated pathophysiology. However, the role of these ncRNAs remains largely unknown. Circular RNAs (circRNAs) include a high number of miRNA-binding sites (miRNA response elements, MREs), which act as miRNA sponges or competing endogenous RNAs (ceRNAs). This study aimed to examine the involvement of long non-coding RNAs (circRNAs) and miRNAs, in AD as potential biomarkers. An expression profile of patients with AD was downloaded from the Gene Expression Omnibus (GEO) database (GSE5281, GSE122603, GSE97760, GSE150693, GSE1297, and GSE161435). Through preliminary data deletion, 163 genes with significant differences, 156 miRNAs with significant differences, and 153 circRNAs with significant differences were identified. Then, 10 key genes, led by MAPT and APM2A1, were identified by the mediation center algorithm, 34 miRNAs with obvious prognosis were identified by the cox regression model, and 16 key circRNAs were selected by the database. Hub circRNAs and mRNAs were selected to create competing endogenous RNA (ceRNA) networks. Finally, GO analysis and clinical information verification of core genes were performed. We found that down-regulated circRNA (hsa_circ_002048) affected the increased expression of multiple miRNAs, which further restricted the expression of key mRNA (AP2M1), which led to AD-related pathology. Together, this study’s data provide a deeper understanding of the circRNA–miRNA–mRNA regulatory mechanisms in AD. Moreover, the ncRNAs discovered here might become novel biomarkers and promising targets for AD drug development.